2014
DOI: 10.1002/hec.3019
|View full text |Cite
|
Sign up to set email alerts
|

Universal Public Finance of Tuberculosis Treatment in India: An Extended Cost‐Effectiveness Analysis

Abstract: Universal public finance (UPF)-government financing of an intervention irrespective of who is receiving it-for a health intervention entails consequences in multiple domains. First, UPF increases intervention uptake and hence the extent of consequent health gains. Second, UPF generates financial consequences including the crowding out of private expenditures. Finally, UPF provides insurance either by covering catastrophic expenditures, which would otherwise throw households into poverty or by preventing diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
187
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(189 citation statements)
references
References 73 publications
1
187
0
1
Order By: Relevance
“…As previously reported [17], there was a preference of private providers. In India, there is large prevalence of private providers, and the healthcare costs in private care are higher than in the public sector [17,18]. Qualitative interviews revealed that a lack of awareness of TB care service availability in the public sector combined with a lack of awareness about TB symptoms, in the underlying milieu of general preference for private facility, the factors including timings of service availability, perception of quality, etc., could have led to this phenomenon of a higher proportion of participants seeking private-sector care.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported [17], there was a preference of private providers. In India, there is large prevalence of private providers, and the healthcare costs in private care are higher than in the public sector [17,18]. Qualitative interviews revealed that a lack of awareness of TB care service availability in the public sector combined with a lack of awareness about TB symptoms, in the underlying milieu of general preference for private facility, the factors including timings of service availability, perception of quality, etc., could have led to this phenomenon of a higher proportion of participants seeking private-sector care.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) The DCP3 project which aims to produce guides to cost effectiveness of healthcare in low-and middle-income countries uses an "Extended Cost Effectiveness" approach in which the insurance benefits of coverage are calculated 6 . This recognises the important financial protection role of the public healthcare system in many poorer countries, where many people are currently exposed to substantial financial risk in the event that they fall ill. (iii) Many stakeholders have argued that current HTA decision rules are failing to fully account for the different sources of value of new antibiotics, which should be rewarded for their innovativeness relative to the current available armamentarium, as drugs with novel mechanisms of action can be expected to hold their own against resistance 7 .…”
Section: Figurementioning
confidence: 99%
“…We therefore see DCEA as encompassing these previous equity weighting methods within a more general framework that provides decision makers with more detailed information about health inequality impacts, rather than as a rival alternative approach. An important emerging source of empirical literature on incorporating health inequality impacts into economic evaluation in low and middle income countries is the 'extended CEA' framework (Verguet et al, 2014). This approach is similar in spirit to DCEA, although simplifies the analysis by (i) focusing on a single distributional variable (wealth quintile group) rather than analysing multiple distributional variables, (ii) setting aside the issue of opportunity costs falling on the health budget by assuming the intervention is funded by the tax system, and (iii) presenting results as a disaggregated 'dashboard' of costs and consequences by social group rather than using inequality indices and social welfare functions to explicitly analyse trade-offs between improving health and reducing unfair health inequality.…”
Section: Other Approachesmentioning
confidence: 99%